The synergy between workforce, students, and lecturers in collaborative learning - Marsofiyati Marsofiyati; Etin Solihatin; Robinson Situmorang (Institute of Advanced Engineering and Science, 2024)
This research focuses on applying technology in collaborative learning, specifically through online platforms that connect students and the workforce. It is objective is to enhance synergy among the workforce, students, and educators to improve learning quality. The case study methodology follows Creswell’s qualitative approach with five key steps: planning the case study; data collection; analysis; result interpretation; and reporting. The research explores innovative online platforms to create a comprehensive and diverse learning experience. Technology enables access to materials, virtual classrooms, e-books, mobile learning, and internship programs, fostering flexible and engaging education. Collaborative learning with workforce participation enhances effectiveness and skills. Students gain work experience related to their fields through active interaction with practitioners. At the same time, educators refine teaching methods and understand workforce demands-the synergy among the workforce, students, and educators’ mutually beneficial relationships. The workforce leverages student resources for problem-solving and innovation, while students enhance their networks. Educators gain input for curriculum improvement. The research enhances education quality, prepares students for the dynamic workforce, and aligns educational programs with industry demands. It emphasizes the importance of collaborative learning, integrating online platforms to increase skill development.